Environmental and food safety standards in the context of trade liberalization: Issues and options - Ulrike Grote; Stefanie Kirchhoff (University of Bonn, Center for Development Research (ZEF), 2001)
The current debate on trade liberalization is accompanied by an increased concern about environmental and food safety issues leading to frictions of different country groups under the World Trade Organization (WTO). This discussion paper aims at shedding more light on some of the issues in the trade and environment debate. It describes the complex process of setting standards, the relevant WTO agreements dealing with technical as well as sanitary and phytosanitary standards and potential outcomes of setting environmental standards-outcomes for the environment, for international trade relations and the competitiveness of countries. The theoretical part shows that under certain assumptions, not only protectionist but also environmental concerns may lead to a political decision for suboptimal standards. Finally, the paper offers a list of alternative policy responses and strategies to tackle environmental issues in the context of international trade. This includes the polluter-pays principle, eco-labeling and other labeling schemes, reducing in- and output subsidies, stronger enforcement of given standards, technical assistance, harmonization and mutual recognition of equivalent standards, and multilateral environmental agreements (MEAs). It is concluded that while no individual strategy proves to be the optimal solution, a mixture of different approaches is needed and care has to be taken to avoid the misuse of environmental standards for protectionist reasons. The participation of developing countries should be increased when setting standards at international level, defining criteria for eco-labels or negotiating MEAs.
Keywords: 330; Environmental Economics and Policy; Food Consumption/Nutrition/Food Safety; International Relations/Trade; Umweltstandard; Lebensmittelsicherheit; Handelsliberalisierung; WTO-Regeln; Internationaler Wettbewerb; Umweltpolitik; Nord-Süd-Beziehungen; Neue Außenhandelstheorie; Zwei-Länder-Modell; Internationale Wirtschaftspolitik; Theorie; Welt